The Effectiveness of using Numbered Heads Together Technique on Students’ Reading Comprehension at VIII Grade of MTs AL-Amien 1 Prenduan Sumenep 2025/2026 - Ahmadi; Ummu Kulsum; Hayyul Mubarok (Pendidikan Agama Islam, 2026)
This study aimed to investigate whether there is a significant effect of using the Numbered Heads Together (NHT) technique on the reading comprehension achievement of the eighth-grade students at MTs Al-Amien 1 Prenduan. The study was motivated by students’ low reading comprehension ability and the need for an instructional technique that could enhance students’ participation and cooperation in English learning activities. This research employed a quantitative approach using a true experimental design, specifically a pre-test and post-test control group design. The population of the study consisted of all eighth-grade students of MTs AL-amien 1 Prenduan Sumenep in the 2025/2026 academic year, totaling 146 students. The sample consisted of two classes: Class VIII-D as the experimental group and Class VIII-E as the control group, with 32 students in each class. The research instrument was a multiple-choice reading comprehension test administered before and after the treatment. The collected data were analyzed using the t-test formula. The findings revealed that the mean score of the pre-test in the experimental group was 70.31, while that of the control group was 73.43. After the implementation of the Numbered Heads Together technique, the mean post-test score of the experimental group increased to 85.93, whereas the control group achieved a mean score of 75.00. The result of the t-test showed that the obtained t-value was 11.277, which was higher than the critical value of the t-table at both the 5% and 1% significance levels. Therefore, the alternative hypothesis was accepted, and the null hypothesis was rejected. In conclusion, the use of the Numbered Heads Together technique was effective and had a significant positive effect on the reading comprehension achievement of the eighth-grade students at MTs Al-Amien 1 Prenduan Sumenep Madures.